bKash Bangladesh : A Fast Start for Mobile Financial Services - Chen, Gregory; Rasmussen, Stephen (World Bank, Washington, DC, 2014)
The first mobile financial service deployments were launched in Bangladesh in mid-2011, and by the end of 2013 they were being used by 22 percent of the adult population (intermedia 2014) - a fast start for a large country of 160 million inhabitants. In 2013 registered mobile financial services accounts in Bangladesh grew faster than in any other country. The bKash board and management are the first to say that there is a long way to go and much still to do to build the business. It needs to stabilize its technology platform to support a much higher volume of transactions. Early fast scale has provided a platform for bKash to take its next steps and has shown that it is possible to create a deeper and more competitive market in Bangladesh.